Efektivitas Terapi Relaksasi Otot Progresif pada Mahasiswa Tingkat Akhir yang Mengalami Stress di Program Studi Ilmu Keperawatan - Rustam, Zulis Noor Rafik; Suhermi, Suhermi; Alam, Rizqy Iftitah; Alam, Rizqy Iftitah (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Covid 19 has brought many changes in human life. Currently, the campus is implementing an online learning system, aka online (in the network). This has an impact on final year students who are writing a thesis which will usually cause stress when compiling a thesis. Therefore, progressive muscle relaxation can reduce stress and learn how to relax tense muscles. The purpose of this study was to determine whether progressive muscle relaxation therapy can relieve or reduce stress levels in final year students. The research design used was quasi experimental. The research design used